PREDIKSI KEBANGKRUTAN DI PT. ARGO PANTES TBK TANGERANG - Deharani Nawastari; Arief Rachmawan Assegaf (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The purpose of this study was to determine how the company's financial condition for the period 2012-2021 and predictions of bankruptcy at PT. Argo Pantes Tbk in 2022. The method used in this research is descriptive statistical analysis method using Altman z-score analysis method. The results show that the financial condition of PT. Argo Pantes Tbk during the period 2012-2021, has a bad financial condition, this is based on the company's average ratio of 0 and some ratios are negative. The results of the